Analyses of Ehrlichia canis and a canine granulocytic Ehrlichia infection. - Rikihisa, Y (1992)
Ehrlichia canis and canine granulocytic Ehrlichia sp. (CGE) infect canine monocytes and granulocytes, respectively. E. canis has been cultured in vitro and used to develop an immunofluorescence assay. CGE has not been cultured, and a serologic assay is not available. The sera of dogs infected with CGE were reported to react with E. canis by immunofluorescence. In this study, the temporal response of immunoglobulin G (IgG) was determined by an enzyme-linked immunosorbent assay (ELISA) with purified E. canis antigen in four dogs experimentally infected with E. canis, in two dogs experimentally infected with CGE, and in one dog infected with E. canis and subsequently infected with CGE. E. canis-infected dogs developed an IgG ELISA result of 1.5 or greater for the optical density signal/noise ratio by 2 months postinfection. CGE challenge of a dog with a previous E. canis infection induced an anamnestic increase in the IgG ELISA result; however, CGE infection alone did not induce a significant IgG ELISA response. Western immunoblot analysis showed that dogs infected with E. canis developed antibodies initially that reacted with low-molecular-mass proteins (30, 24, and 21 kDa) and subsequently with higher-molecular-mass proteins (160, 100, 78, 64, 47, and 40 kDa). In contrast, CGE-infected dogs showed reactions with the same higher-molecular-mass proteins of E. canis but, unlike E. canis-infected dogs, not with the low-molecular-mass proteins of E. canis. Of 10 serum samples collected in the field of Indonesia from dogs with tropical canine pancytopenia, all had an optical density signal minus noise value of 2.54 or greater in the IgG ELISA and reacted with E. canis antigen in a pattern similar to that of serum samples from dogs experimentally infected with E. canis in Western immunoblotting. This study suggests that the IgG ELISA and Western immunoblotting with purified E. canis as the antigen are useful in distinguishing between E. canis and CGE infections in dogs.